DETERMINAN FAKTOR-FAKTOR KINERJA KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023) - Fatmaningtyas, Sastria; Setiawati, Erma (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine the effect of sales growth, capital structure, firm size, liquidity, and total asset turnover on financial performance. In this study, sales growth is proxied by sales growth, capital structure is proxied by debt to equity ratio, firm size is proxied by size, liquidity is proxied by current ratio, and total asset turnover is proxied by total asset turnover. This study was conducted on consumer sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sampling technique used in this study was purposive sampling technique. The sample used in this study was 45 companies and was carried out for 3 years, resulting in 135 data. The data analysis technique used was multiple linear regression analysis. The results showed that the variables of sales growth and capital structure did not affect financial performance, while firm size, liquidity, and total asset turnover did affect financial performance.